633 Dual-targeting of 4–1BB and OX40 with an ADAPTIR™ bispecific antibody enhances anti-tumor responses to solid tumor. (9th November 2020) - Nelson, Michelle; Miller, Robert; Blahnik-Fagan, Gabriele; Loh, Lauren; Citters, Danielle Van; Misher, Lynda; Sprague, Megan; Dasovich, Maria; Barber, Irene; Maggiora, Kathy; Gruswitz, Franz; Woodruff, Brian; et al.
Abstract : Background: 4-1BB (CD137) and OX40 (CD134) are critical activation-induced co-stimulatory receptors that regulate immune responses of activated T and NK cells by enhancing proliferation, cytokine production, survival, and cytolytic activity. A superagonist 4-1BB antibody has shown clinical activity but severe toxicities. APVO603, is a 4-1BB x OX40 targeting bispecific antibody with conditional agonism, activating these receptors only when both are co-engaged. The Fc portion was mutated to eliminate FcγR-mediated interactions. Co-stimulation through 4-1BB and OX40 has the potential to amplify the cytotoxic function and the number of activated T and NK cells in multiple solid tumor indications. 1–2 Methods scFv binding domains to 4-1BB and OX40 were optimized to increase affinity, function and stability, and then incorporated into the ADAPTIR™ bispecific antibody platform to produce the APVO603 lead candidate. NF-κB/luciferase reporter cell lines expressing OX40 or 4-1BB were initially used to assess the agonistic function of APVO603's binding domains. Primary PBMC were sub-optimally stimulated with an anti-CD3 antibody and T and NK cell proliferation was assessed using Cell TraceTM-labelled PBMC. Cytokine secretion was measured at 48 hrs using Luminex-based assays. For in vitro tumor lysis studies, PBMC were co-cultured with tumor cells expressing a tumor-associated antigen (TAA) and activated with TAA x CD3 bispecific protein. 7-AAD expression was assessed on tumor cells at 72 hrs. The in vivo therapeutic efficacy of APVO603 was evaluated using a murine MB49 bladder cancer model in human 4-1BB and OX40 double knock-in mice. Results: APVO603 stimulates 4-1BB and OX40 NF-κB/luciferase reporter activity in a dose-dependent manner, and is strictly dependent on engagement of the reciprocal receptor to elicit 4-1BB or OX40 activity. In primary PBMC assays, APVO603 induces synergistic proliferation of CD4+, CD8+ T and NK cells when compared to OX40 or 4-1BB monospecific molecules with a wt Fc, either individually or in combination. Additionally, APVO603 enhances proinflammatory cytokine production and granzyme B expression, and augments in vitro tumor cell lysis induced by a TAAx CD3 engager. In vivo, APVO603 reduces growth of established MB49 tumors in human 4-1BB and OX40 double knock-in mice. Conclusions: APVO603 is a dual-agonistic bispecific antibody that augments the effector function of activated CD4+ and CD8+ T and NK cells in a dose-dependent manner, and reduces growth of established tumors in vivo. This preclinical data, demonstrates conditional dual stimulation of 4-1BB and OX40 and supports further development of APVO603, a promising immuno-oncology therapeutic with potential for benefit in solid tumors. Ethics Approval: Treatment of study animals was in accordance with conditions specified in the Guide for the Care and Use of Laboratory Animals, and the study protocol (ACUP 20) was approved by the Institutional Animal Care and Use Committee (IACUC). References: Bandyopadhyay S, Long M, Qui H, Hagymasi A, Slaiby A, Mihalyo M, Aguila H, Mittler R, Vella A, Adler A. Self-antigen prevents CD8 T cell effector differentiation by CD134 and CD137 dual costimulation. J Immunol 2008;181(11):7728–37. Ryan J, Mittal P, Menoret A, Svedova J, Wasser J, Adler A, Vella A. A novel biologic platform elicits profound T cell costimuloaroty activity and antitumor immunity in mice. Cancer Immunol Immunother 2018;67(4):605–613.